LEİBNİZ VE MCTAGGART'IN CEVHERİN BİRLİĞİ SORUNUNA YAKLAŞIMLARI - Aliye Kovanlıkaya (Felsefe Dünyası)
For McTaggart, existence can be classified into three categories: substance, quality and relation. Neither one of these can be reduced to one another. Substance, in such a framework, is described as that which has characteristics i.e., qualities and relations without itself being a characteristic. McTaggart claims that every substance is a whole that is differentiated into infinite number of parts each of which is again a substance. The substance that has all other substances as its parts is Universe and there is no simple substance. Each substance is